"Our Journey, Our Choice, Our Future": Huu‐ay‐aht First Nations' Self‐Government enacted through the Maa‐nulth Treaty with British Columbia and Canada. Issue 4 (15th April 2019) - Sloan Morgan, Vanessa; Castleden, Heather; ,
Abstract: In 2011, Huu‐ay‐aht First Nations became one of five Nuu‐chah‐nulth Nations on the west coast of Vancouver Island in Canada to implement the Maa‐nulth Treaty with the Province of British Columbia and Canada. Modern treaties are dense and lengthy legal documents that exhaustively set out the obligations of each signatory party. They are heavily criticised for being unjust extensions of colonialism that limit Indigenous self‐determination and transform homelands under settler colonial property regimes. Yet, some First Nations accept these agreements as their chosen path for self‐government in state structures. We document Huu‐ay‐aht First Nations' decision‐making that resulted when the Maa‐nulth Treaty was implemented and replaced the Indian Act by analysing the Maa‐nulth Treaty and interviews conducted with Huu‐ay‐aht First Nations leadership. We demonstrate how ʔiisaak (respect) and ʔuuʔałuk (taking care of) guided Huu‐ay‐aht First Nations' self‐government, while nesting this discussion in the complexities and critiques of modern treaties.